Polymorphism in the serotonin transporter gene polymorphisms (5-HTTLPR) modifies the association between significant life events and depression in people with multiple sclerosis - Saul, A; Taylor, B; Simpson, Jr, S; Ponsonby, A-L; Blizzard, L; Dwyer, T; McMorran, B; Wood, B; van der Mei, IAF (SAGE Publications, 2018)
Background: In the general population, variation in the serotonin-transporter-linked polymorphic region (5-HTTLPR) has been shown to modify the association between stressful events and depression/anxiety. This has not been examined in people with multiple sclerosis (MS). Objective: We examined the interaction between significant life events (SLE), 5-HTTLPR and depression/anxiety. Methods: A population-based longitudinal cohort of 198 people with MS was followed biannually for 2.5 years. Depression and anxiety symptoms were measured at each review using the Hospital Anxiety and Depression Scale (HADS). SLEs were assessed using a questionnaire based on the Social Readjustment Rating Scale. Results: We found an interaction between SLE load in the previous 12 months and functional variation in the 5-HTTLPR allele type in predicting depression, with the association between SLE load and depression being stronger for those with S/S allele type (β = 0.21 (95% confidence interval (CI): 0.09–0.33) per 10-unit increase) and S/L (β = 0.14 (95% CI: 0.05–0.24)) compared to L/L allele type (β = 0.04 (95% CI: −0.05 to 0.24); pinteraction < 0.001). No convincing evidence of an interaction was found with anxiety. Conclusion: We found that the association between SLE load and MS depression severity was stronger among those with one or two copies of the short allele of the 5-HTTLPR. The identification of a gene–environment interaction between SLEs and depression in a population where depression is partly disease-driven is novel.